ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN DI TOKO ZAABAI CRAFT - Barima, Hima; Melani, Fauziah; Rachindratama, Joda; Azizah, Ukhti (Perwira Journal of Economics & Business, 2023)
The purpose of this study was to determine the analysis of marketing strategy to increase sales at Zaabai Craft Stores. This research was conducted in Purbalingga District, Purbalingga Regency. The implementation time is planned for one week in November 2022. This research method uses a qualitative descriptive analysis approach to find out what kind of strategy is used by the Zaabai Craft Shop. The type of data in this research is qualitative data. Meanwhile, the data source is primary data. Data collection methods are carried out by means of observation, surveys, and interviews. The result of the research is that the Zaabai Craft Store has implemented a good strategy in maintaining its business. Such as adding craft materials by looking for additional suppliers, researching consumer needs, a clean and comfortable place and good quality goods at low prices. Meanwhile, the supporting factors for the marketing strategy at the Zaabai Craft Shop are good promotion management, market research and friendly and courteous service. Although there are also inhibiting factors related to craft materials that are still incomplete. However, these inhibiting factors can be overcome by looking for additional suppliers to complement materials that are not yet available at the Zaabai Craft Store.